Preformulation Studies and Bioavailability Enhancement of Curcumin with a 'Two in One' PEG-β-Cyclodextrin Polymer - Ádám Haimhoffer; Eleftheria Dossi; Monika Béresová; Ildikó Bácskay; Judit Váradi; Ashfaq Afsar; Ágnes Rusznyák; Gábor Vasvári; Ferenc Fenyvesi (MDPI AG, 2021)
Drug delivery systems are used to improve the biopharmaceutical properties of curcumin. Our aim was to investigate the effect of a water-soluble 'two in one' polymer containing covalently bonded PEG and βCD moieties (βCPCD) on the solubility and bioavailability of curcumin and compare it to a polymeric β-cyclodextrin (βCDP) cross-linked with epichlorohydrin. Phase-solubility and dynamic light scattering (DLS) experiments showed that the solubility of curcumin increased significantly in 10 m/m % βCPCD and βCDP solutions, but βCPCD-curcumin particles had higher hydrodynamic volume. The formation of the βCPCD-curcumin complex in solution and sedimented phase was confirmed by NMR spectroscopy. Biocompatibility and permeability experiments were performed on Caco-2 cells. Polymers did not show cytotoxicity up to 10 m/m % and βCPCD significantly increased the permeability of curcumin. DLS measurements revealed that among the interaction of polymers with mucin, βCPCD formed bigger aggregates compared to βCDP. Curcumin complexes were lyophilized into capsules and structurally characterized by micro-CT spectroscopy. Drug release was tested in a pH 1.2 medium. Lyophilized complexes had a solid porous matrix and both βCPCD and βCDP showed rapid drug release. βCPCD provides an opportunity to create a swellable, mucoadhesive matrix system for oral drug delivery.